2013
DOI: 10.1007/s00259-013-2351-9
|View full text |Cite
|
Sign up to set email alerts
|

Functional imaging of head and neck squamous cell carcinoma with diffusion-weighted MRI and FDG PET/CT: quantitative analysis of ADC and SUV

Abstract: PurposeHead and neck squamous cell carcinoma (HNSCC) may cause a decreased apparent diffusion coefficient (ADC) on diffusion-weighted magnetic resonance imaging (DW MRI) and an increased standardized uptake value (SUV) on fluorodeoxyglucose (FDG) positron emission tomography (PET/CT). We analysed the reproducibility of ADC and SUV measurements in HNSCC and evaluated whether these biomarkers are correlated or independent.MethodsThis retrospective analysis of DW MRI and FDG PET/CT data series included 34 HNSCC i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
78
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 47 publications
(82 reference statements)
7
78
0
Order By: Relevance
“…Interobserver reproducibility was assessed by the interobserver correlation coefficient. 30 An interobserver correlation coefficient value of Ͻ0.40 indicated poor reproducibility, 0.40 -0.59 indicated fair reproducibility, 0.60 -0.74 indicated good reproducibility, and Ͼ0.74 indicated excellent reproducibility. 31 An independent t test was used to compare significant differences between the AIs from ASL by observers 1 and 2 and between the AIs from SPECT and ASL.…”
Section: Discussionmentioning
confidence: 99%
“…Interobserver reproducibility was assessed by the interobserver correlation coefficient. 30 An interobserver correlation coefficient value of Ͻ0.40 indicated poor reproducibility, 0.40 -0.59 indicated fair reproducibility, 0.60 -0.74 indicated good reproducibility, and Ͼ0.74 indicated excellent reproducibility. 31 An independent t test was used to compare significant differences between the AIs from ASL by observers 1 and 2 and between the AIs from SPECT and ASL.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, apparent diffusion coefficient (ADC) maps calculated from DW-MRI sequences are being increasingly used to provide quantitative data for head and neck lesion diagnosis. In malignant lesions, the DW-MRI signal increases and signal loss is observed on ADC maps (5,7,8). Many researchers benefited from this feature of DW-MRI and evaluated the effectiveness of DW-MRI for head and neck lesion identification, benign-malignant differentiation, and characterization of malignant lesions (9)(10)(11).…”
mentioning
confidence: 99%
“…This study also reported a negative correlation, however, the study included only 7 patients with different tumor subsites (6). The existing studies in the literature either are not performed on an integrated PET/MR scanner or do not include patients with head and neck tumors (21,22,(34)(35)(36)(37)(38). The nonsignificant correlation found across patients suggests that information on glucose metabolism and cellularity from only 1 voxel, the voxel within the tumor either with the highest 18 F-FDG uptake (SUV max ) or with the lowest diffusion (ADC min ), may be too crude to adequately describe the tumor and depict a potential correlation.…”
Section: Discussionmentioning
confidence: 78%